Negotiating Economic Partnership Agreements: Agriculture - Fautrel, Vincent; Alpha, Arlene (ECDPM/CTA, 2007)
The aim of this InBrief series is to identify the key issues at stake within the various chapters of the Economic Partnership Agreements (EPAs) being negotiated between the European Union and six African, Caribbean and Pacific (ACP) regional groupings. This InBrief on Agriculture is an initiative by the European Centre for Development Policy Management (ECDPM) and the Technical Centre for Agricultural and Rural Cooperation ACP-EU (CTA).